The Nottingham Fatigue After Stroke (NotFAST) Study: results from follow-up six months after stroke - Drummond, Avril E.R.; Hawkins, Loiuse; Lincoln, Nadina; Sprigg, Nikola; Tyrrell, Pippa; Worthington, Esme (Taylor and Francis, 2017)
Background: Post-stroke fatigue is common and disabling. Objectives: The aim of NotFAST was to examine factors associated with fatigue in stroke 3 survivors without depression, six months after stroke. Methods: Participants were recruited from four UK stroke units. Those with high levels of 5 depressive symptoms (score ≥7 on Brief Assessment Schedule Depression Cards) or aphasia were excluded. Follow-up assessment was conducted at six months after stroke. They were assessed on the Fatigue Severity Scale, Rivermead Mobility Index, Nottingham Extended Activities of Daily Living scale, Barthel Index, Beck Anxiety Index, Brief Assessment Schedule Depression Cards, Impact of Event Scale-Revised, and Sleep Hygiene Index. Results: Of the 371 participants recruited, 263 (71%) were contacted at six months after stroke and 213 (57%) returned questionnaires. Approximately half (n=109, 51%) reported fatigue at six months. Of those reporting fatigue initially (n=88), 61 (69%) continued to report fatigue. ‘De novo’ (new) fatigue was reported by 48 (38%) of those not fatigued initially. Lower Nottingham Extended Activities of Daily Living scores and higher Beck Anxiety Index scores were independently associated with fatigue at six months. Conclusions: Half the stroke survivors reported fatigue at six months post-stroke. Reduced independence in activities of daily living and higher anxiety levels were associated with the level of fatigue. Persistent and delayed onset fatigue may affect independence and participation in rehabilitation, and these findings should be used to inform the development of appropriate interventions.